The development and characterization of caprine infection models of melioidosis - Soffler, Carl, author; Bowen, Richard A., advisor; Aboellail, Tawfik A., committee member; Dow, Steven W., committee member; Schweizer, Herbert P., committee member; Van Metre, David C., committee member (Colorado State University. Libraries, 2012)
Melioidosis, the disease resulting from infection with Burkholderia pseudomallei, is a serious emerging infectious disease endemic to Southeast Asia and Northern Australasia and a leading infectious cause of death in the former. Additionally, B. pseudomallei has been designated a Category B Select Agent by the United States Centers for Disease Control and Prevention because of its potential use in bioterrorism, which has led to intensive research on inhalational models of murine melioidosis. Natural infection is believed to occur predominantly through percutaneous inoculation or inhalation in the rainy season in endemic areas, with infection following oral exposure occurring to a lesser extent. However, the actual importance of each route of infection in natural disease is unknown. Studies examining the comparative pathogenesis of melioidosis in regards to the route of infection are generally lacking, particularly in naturally affected species. A goat model was selected as it provides the opportunity to study the importance of the route of infection and its effect on disease pathogenesis in a naturally affected species. Disease and outcome can be evaluated relative to natural presentations in both human and goat populations as goats and humans exhibit a similar epizootiology/epidemiology of melioidosis, which corresponds to similar environmental exposure to B. pseudomallei within its endemic range. Furthermore, the larger body size of goats allows for human-relevant clinical monitoring as well as longer-term serial evaluation of disease progression and therapy in individual animals. Using a caprine model system, we have investigated the pathogenesis of infection following intratracheal aerosol and percutaneous exposure to 104 delivered colony forming units (CFU) of B. pseudomallei. Disease was observed in all animals following infection. Acute disease was more severe in aerosol infected goats, but both groups tended to develop subacute to chronic active disease, with percutaneously infected goats showing regression of lesions at the later time points. Percutaneously infected goats generally exhibited more variable clinical signs, hematologic changes, and gross pathology, but often had histologic lesions with more severe changes. Dissemination from the site of infection was much more rapid in the percutaneously infected animals, with bacteria detectable in the lungs and spleen as early as Day 2 post-infection (PI) and gross abscessation evident in distant sites as early as Day 7 PI. Extrapulmonary dissemination after aerosol infection appeared to occur around Day 7 with splenic or renal abscesses not grossly detectable until day 14. Lesion development was closely associated with a leukocytoclastic vasculitis observed in affected tissues in both aerosol and percutaneous infection. Pulmonary involvement was evident in all but one percutaneously infected goat (Day 2 PI) by culture or the presence of histologic lesions. The rapid dissemination of B. pseudomallei after percutaneous inoculation challenges the perception that inhalational melioidosis is more severe in presentation or will affect the lungs more frequently than percutaneous infection. The findings presented here provide a detailed clinical, radiographic, and pathologic description of the pathogenesis of subacute to chronic aerosol and percutaneous caprine melioidosis. However, acute presentations are possible in association with concurrent disease or debility, suggesting that the caprine model system may be amenable to the incorporation of risk factors to increase susceptibility/acute disease as typically seen in human melioidosis. It is hoped these models will help broaden the scope of melioidosis research to fill remaining voids, particularly in the areas immunology, vaccine development, and evaluation of novel antimicrobial therapeutics through the comparative study of disease. Additionally, melioidosis in goats remains a current problem in the regions of Southeast Asia and Northern Australia with enzootic and epizootic disease causing economic losses. Any knowledge gained from the use of these models in regards to improved diagnosis, preventive measures, and vaccination could be directly applicable to the management of these goat populations and advancing public health.
Keywords: animal model; pseudomallei; percutaneous; melioidosis; pathogenesis; aerosol